2007
DOI: 10.1056/nejmsb071889
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Expansion of the Health Workforce in Response to the HIV Epidemic

Abstract: T h e n e w e ng l a n d j o u r na l o f m e dic i n e

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
141
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(146 citation statements)
references
References 10 publications
3
141
0
1
Order By: Relevance
“…The argument that decentralisation of ART services is impossible because of lack of trained staff , weak infrastructure, and poor drug security is unpersuasive; health centres in rural areas can achieve good treatment outcomes with ART. 122 International policy calls for task shifting in HIV care 41,112,123 have been heeded, and eff ective nurse-driven ART in primary care is already a reality. 124 At least in the short-to-medium term, equivalent ART outcomes can be achieved through a public health approach without the need for sophisticated laboratory monitoring.…”
Section: Collaborationmentioning
confidence: 99%
“…The argument that decentralisation of ART services is impossible because of lack of trained staff , weak infrastructure, and poor drug security is unpersuasive; health centres in rural areas can achieve good treatment outcomes with ART. 122 International policy calls for task shifting in HIV care 41,112,123 have been heeded, and eff ective nurse-driven ART in primary care is already a reality. 124 At least in the short-to-medium term, equivalent ART outcomes can be achieved through a public health approach without the need for sophisticated laboratory monitoring.…”
Section: Collaborationmentioning
confidence: 99%
“…Similarly, the number of nurses per 100 000 population is 59 in Malawi compared with 937 in the USA, 995 in Canada and 1212 in the United Kingdom. 4,5 The scale-up of antiretroviral treatment (ART) in subSaharan Africa has highlighted the human resource challenge of delivering and sustaining this life-saving intervention. [6][7][8] Consequently, the delegation of medical and health service duties from higher to lower cadres or new cadres, known as task shifting, is increasingly promoted as a coping mechanism for general and specific human resource shortages.…”
Section: Introductionmentioning
confidence: 99%
“…2 Centre for Infectious Disease Research in Zambia, Lusaka, Zambia. 3 University of Alabama, Birmingham, AL, USA.…”
Section: Author Detailsmentioning
confidence: 99%
“…Operational research studies have recently demonstrated the feasibility of large scale ART programs within public sector, based on satisfactory clinical outcomes such as survival and treatment success [1][2][3]. While population health outcomes are a natural focus of health services research seeking to determine the effectiveness of a public health intervention, they are determined by multiple factors classified under "quality of process" and "quality of structure" [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation